2011
DOI: 10.1007/s10554-011-9929-8
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of pulse wave velocity measurements with phase contrast magnetic resonance and applanation tonometry

Abstract: Increased aortic pulse wave velocity (PWV) results from loss of arterial compliance and is associated with unfavorable outcomes. Applanation tonometry (AT) is the most frequently applied method to assess PWV and deduce aortic compliance. The goal of this study was to compare the reproducibility of PWV measurements obtained with: (1) cross-correlation analysis of phase contrast magnetic resonance (PCMR) velocity data, and (2) applanation tonometry (AT). PWV was measured twice with each modality in 13 normal you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
2
8
1
Order By: Relevance
“…The current study showed lower PWV in the younger healthy cohort compared with older patients at risk for CVD, as expected [ 1 , 8 ]. The current study also showed slightly higher PWV for the healthy young cohort compared with data from an equivalent age group in a recent study including PWV in only the aortic arch (4 m/s), [ 10 ] but lower than a study also including parts of the abdominal aorta (5.6 m/s) [ 17 ]. This difference may be explained by that measurements for PWV are related to the elastic properties of the vessels, which vary along the arterial tree, with more elastic proximal segments and stiffer distal segments.…”
Section: Discussioncontrasting
confidence: 46%
“…The current study showed lower PWV in the younger healthy cohort compared with older patients at risk for CVD, as expected [ 1 , 8 ]. The current study also showed slightly higher PWV for the healthy young cohort compared with data from an equivalent age group in a recent study including PWV in only the aortic arch (4 m/s), [ 10 ] but lower than a study also including parts of the abdominal aorta (5.6 m/s) [ 17 ]. This difference may be explained by that measurements for PWV are related to the elastic properties of the vessels, which vary along the arterial tree, with more elastic proximal segments and stiffer distal segments.…”
Section: Discussioncontrasting
confidence: 46%
“…Some of the limitations in determining variations in regional vessel wall motion can be addressed through the use of cine phase contrast magnetic resonance imaging (PCMR) to assess PWV at multiple axial locations along the length of the aorta . Previously, axial cine PCMR has been used to evaluate variability in distensibility and compliance with respect to axial location . However, these methods are unable to measure heterogeneities in aortic distension circumferentially (ie, around the vessel) or radially (ie, through the aortic wall).…”
mentioning
confidence: 99%
“…10 Previously, axial cine PCMR has been used to evaluate variability in distensibility and compliance with respect to axial location. 11,12 However, these methods are unable to measure heterogeneities in aortic distension circumferentially (ie, around the vessel) or radially (ie, through the aortic wall). Circumferential and radial mechanical heterogeneity may be critical in risk stratification and therapeutic planning for certain aortic pathologies (eg, rupture risk in abdominal aortic aneurysms [AAA]), which likely depend on local, patient-specific biomechanics.…”
mentioning
confidence: 99%
“…Grotenhuis et al [ 9 ] evaluated the reproducibility by repeating acquisitions on the same day and reported a coefficient of variation of 9% for PWV assessment in the total aorta by CMR. In a study by Suever et al [ 27 ], reproducibility of CMR-assessed PWV was compared to applanation tonometry by performing repeated studies on volunteers on the same day. However, no data has been published for repeated acquisitions on separate days, therefore information on the physiological variation of this marker is missing, although CMR-assessed PWV is widely used in clinical research.…”
Section: Discussionmentioning
confidence: 99%